Intra-system reliability of SICS: Video-tracking system (Digital.Stadium®) for performance analysis in soccer - Beato, M.; Jamil, M. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The correct evaluation of external load parameters is a key factor in professional soccer. The instrumentations usually utilised to quantify the external load parameters during official matches are video-tracking systems (VTS). VTS is a technology that records two-dimensional position data (x and y) at high sampling rates (over 25 Hz). The aim of this study was to evaluate the intra-system reliability of Digital.Stadium® VTS. METHODS: Twenty-eight professional male soccer players taking part in the Italian Serie A (age 24±6 years, body mass 79.5±7.8 kg, stature 1.83±0.05 m) during the 2015/16 season were enrolled in this study (team A and team B). Video-analysis was done during an official match and data analysis was performed immediately after the game ended and then replicated a week later. RESULTS: This study reported a near perfect relationship between the initial analysis (analysis 1) and the replicated analysis undertaken a week later (analysis 2). R2 coefficients were highly significant for each of the performance parameters, P<0.001. This study reported a mean TD=8095±3271 and 8073±3263 m in analysis 1 and analysis 2, respectively. Players reported a mean distance covered over 25 w/kg equivalent to 1304±673 m and 1294±672 m, and they reported a mean metabolic power of 9.65±1.64 w/kg and 9.58±1.61 w/kg, in analysis 1 and analysis 2, respectively. CONCLUSIONS: The findings reported in this study underlined that all data reported by Digital.Stadium® VTS showed high levels of absolute and relative reliability.